Comparative analysis and the impact of the implementation of the profit-sharing scheme of gross split oil and gas on the investment value of upstream oil and gas - Danny Ivan Rantung; Nouke Sysca Oroh; Ika Prayanthi (Trigin Publisher, 2022)
This research wants to prove whether when Indonesia implemented the rules for implementing the gross split profit sharing scheme in 2017 it had an impact on decreasing upstream oil and gas investment in the following years. Is there a significant difference regarding this upstream oil and gas investment before and after the determination of the implementation of the gross split profit sharing scheme. What are the trends in matters related to upstream oil and gas activities starting from upstream oil and gas investment values, oil, and gas production, signing of new contracts both conventional and non-conventional oil and gas, oil and gas reserves, and oil and gas drilling charts. Using quantitative descriptive research, proves that there is no significant difference in the value of stock investment both before and after the implementation of the gross split profit sharing scheme in 2017 with some interesting trend descriptive analysis. For future researchers, they can conduct research on a longer period in the coming years to get a better trend pattern.